PARTIES AND FORMS OF HUMOR MANIFESTATION OF MENTAL DISORDERS - Krupelnitska, Lyudmila; Shportun, Oksana (PSYCHOLOGICAL JOURNAL, 2016)
In the article the psychological analysis of the two sides of humour – generation and perception, as well as forms of humour, which in various forms of mental disorders have their own specifics, are carried out. Theoretical installations, which should be the basis of empirical studies of humour among people with mental disorders are analysed. Based on the definition of humour as the highest mental function it is argued that generation of humour is a process of active creation of specific humorous attitude to certain content that is based on the ability to perception and reproduction of comic detection, overcoming or removing contradictions and their presentation. If it is observed the perception of humour then it means to reflect the process and results of detection, overcoming or removing contradictions based on comic perception and detection. Perception of humour is also an active process, but this activity is of other field. If the generation of humour is a production activity, then the perception of humour is a “reflexive” activity. Furthermore the perception of humour is impossible without the same research process of material to form the humorous attitude, which is occurred during the generation of humour. However, the “generator” of humour is a source of such material, and the recipient carries out this “research” after paying attention to comic aspect of the situation that has already been opened by someone else. Both sides of humour are involved in the process of personal regulation and are different sides of the same mental function. In various forms of mental disorders these sides of humour can change irregularly and inconsistently. Thus, in neurotic, stress-related and somatoform disorders the ability to perceive humour is operated at a sufficient level, the ability to generate humour is partially broken: persons with such forms of mental disorders can detect the satisfactory level of functioning of generative aspects of humour in writing, but the reduced level of functioning in oral form. At the same time, there is evidence that the high level of anxiety correlates negatively with comic effect in the perception of humour. However, the authors point to mixed and diverse relationships between perceptions of humour and anxiety. In schizophrenia the ability for perception (recognition) of humour is reduced, despite the fact that generative side of humour can be presented at the satisfactory level of functioning. In general, the studies of humour in clinical psychology can be combined in two approaches: quantitative and qualitative. The first approach fixes the idea of general decline of humour with in psychopathology. In the second approach it is focused on the qualitative specifics of humour in patients of different nosological groups. The violation of different sides and aspects of humour expression, actually, is considered to a greater extent in the second approach concerning the quality of specificity and mechanisms of changes that occur during the development of disease.